Vibration of Discrete and Continuous Systems - Shabana, Ahmed (Mechanical Engineering Series,, 2019)
This revised, updated textbook adds new focus on computational methods and the importance of vibration theory in computer-aided engineering to fundamental aspects of vibration of discrete and continuous systems covered in the previous two editions of Vibration of Discrete and Continuous Systems. Building on the book's emphasis on the theory of vibration of mechanical, structural, and aerospace systems, the author's modifications, including discussion of the sub-structuring and finite element formulations, complete the coverage of topics required for a contemporary, second course following Vibration Theory. The textbook is appropriate for both upper-level undergraduate and graduate courses. Expands coverage by more than 200 pages over the previous edition; Grounds detail of vibration within discrete and continuous systems with thorough references to the theory of vibration; Explains coverage of computational methods in the vibration analysis; Illustrates the use of the finite element method and sub-structuring techniques in the vibration analysis; Reinforces concepts with over 200 end-of-chapter problems; Facilitates readers' digestion of critical concepts using matrix methods to present some advanced vibration topics in a tractable manner.